Asymptomatic isolated intramuscular cysticercosis in diabetic patient: a case report - Dwipayana, Putu Aditya; Adrian, Steven Johanes; Diyana, Made Wirama (International Journal of Advances in Medicine, 2022)
Cysticercosis is an endemic disease in multiple areas of the world, caused by ingestion of embryonated eggs of Taenia solium. We reported a case of a 66-year old diabetic male presenting with decrease of consciousness and “rice grain” calcification in both hemithorax and neck soft tissue region, without findings of cysticercosis in computed tomography (CT) scan. Cysticercosis most commonly affects the central nervous system, causing neurocysticercosis (NCC), while solitary intramuscular cysticercosis without involvement of the central nervous system is rare. Treatment of cysticercosis is indicated for symptomatic patients, including NCC surgery is indicated in patients with neurovascular compromise caused by growth of cyst. Recognizing the signs and symptoms of cysticercosis is crucial for diagnosis and treatment in endemic areas where Taenia solium is prevalent.